Transcatheter Mitral Valve Replacement in High-Surgical Risk Patients: A Single-Center Experience and Outcome - Fatma A. Taha; Hesham Naeim; Fareed Alnozha; Osama Amoudi; Reda Abuelatta (Journal of Interventional Cardiology)
Background. Re-operative mitral valve (MV) replacement is a high-risk procedure, therefore, transcatheter MV replacement (TMVR) is a promising therapeutic option. Aim. In this study, we aimed to evaluate the feasibility and safety of TMVR in patients with high surgical risk with degenerated mitral bioprostheses (TMViV), failed surgical rings (TMViR), and mitral annular calcification (TMViMAC). Methods. This is a retrospective cohort study that enrolled patients with high surgical risk who underwent TMVR from February 2017 to September 2020. The TMVR procedure was performed using Edwards SAPIEN-3 valves through the transseptal approach. Results. Sixty-four patients aged 62.7 ± 16.1 years with an STS score of 9.2 ± 3.7% underwent TMVR [35 (55%) TMViV, 16 (25%) TMViR, and 13 (20%) TMViMAC]. Mitral stenosis was more frequent in TMViV, mitral regurgitation was more frequent in TMViR, and combined mitral stenosis and regurgitation were more frequent in TMViMAC (P<0.05). The MV gradient was 14.3 ± 5.3 mmHg and the MV area was 1.5±0.6 cm2. The 29 mm valve was frequently used in TMViV and TMViMAC, while the 23 mm valve was frequently used in TMViR (P=0.003∗). The procedural and fluoroscopy times were 58.7 ± 8.9 and 41.1 ± 8.2 minutes, respectively. Technical success was reported in 62 (98.4%) patients; 1 TMViR patient experienced valve embolization and salvage surgery, and 1 TMViMAC patient experienced slight valve malposition. At 3 months, 2 (3.1%) patients showed valve thrombosis (treated with anticoagulation), and 1 (1.6%) patient developed a paravalvular leak (underwent surgical MV replacement). At 6 months, 3 (4.7%) patients showed valve degeneration (underwent surgical MV replacement). Throughout follow-up, no patient exhibited mortality. Conclusions. TMVR is a feasible and safe approach in patients with high surgical risk. TMViV and TMViR are reasonable as the first treatment approaches, and TMViMAC seems encouraging.